Graphene Nanocoating: High Quality and Stability upon Several Stressors. (September 2021) - Rosa, V.; Malhotra, R.; Agarwalla, S.V.; Morin, J.L.P.; Luong-Van, E.K.; Han, Y.M.; Chew, R.J.J.; Seneviratne, C.J.; Silikas, N.; Tan, K.S.; Nijhuis, C.A.; Castro Neto, A.H.
Titanium implants present 2 major drawbacks—namely, the long time needed for osseointegration and the lack of inherent antimicrobial properties. Surface modifications and coatings to improve biomaterials can lose their integrity and biological potential when exposed to stressful microenvironments. Graphene nanocoating (GN) can be deposited onto actual-size dental and orthopedic implants. It has antiadhesive properties and can enhance bone formation in vivo. However, its ability to maintain structural integrity and quality when challenged by biologically relevant stresses remains largely unknown. GN was produced by chemical vapor deposition and transferred to titanium via a polymer-assisted transfer technique. GN has high inertness and did not increase expression of inflammatory markers by macrophages, even in the presence of lipopolysaccharides. It kept high coverage at the top tercile of tapered dental implant collars after installation and removal from bone substitute and pig maxilla. It also resisted microbiologically influenced corrosion, and it maintained very high coverage area and quality after prolonged exposure to biofilms and their removal by different techniques. Our findings show that GN is unresponsive to harsh and inflammatory environments and that it maintains a promising level of structural integrity on the top tercile of dental implant collars, which is the area highly affected by biofilms during the onset of implant diseases. Our findings open the avenues for the clinical studies required for the use of GN in the development of implants that have higher osteogenic potential and are less prone to implant diseases.